2020
DOI: 10.1021/acs.jafc.9b06793
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antifungal Evaluation of Neocryptolepine Derivatives against Phytopathogenic Fungi

Abstract: Neocryptolepine is an alkaloid isolated from traditional African herbal medicine Cryptolepis sanguinolenta, and its broad spectrum of biological activities has been illuminated in past decades. In this study, neocryptolepine and its derivatives (1–49) were designed and synthesized from economical and readily available starting materials. Their structures were confirmed by proton nuclear magnetic resonance, carbon nuclear magnetic resonance, and mass spectrometry. The synthesized compounds were screened for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 28 publications
4
52
0
1
Order By: Relevance
“…The antifungal activity of the synthetic compounds was evaluated in vitro against the ten phytopathogenic fungi using a mycelia growth inhibition method [38]. All the β-PQA salts were dissolved in DMSO (dimethyl sulfoxide) and then added to PDA medium that was prepared and sterilized to obtain a series of concentrations (200, 100, 50, 25, 12.5, 6.25 and 3.125 µg/mL).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…The antifungal activity of the synthetic compounds was evaluated in vitro against the ten phytopathogenic fungi using a mycelia growth inhibition method [38]. All the β-PQA salts were dissolved in DMSO (dimethyl sulfoxide) and then added to PDA medium that was prepared and sterilized to obtain a series of concentrations (200, 100, 50, 25, 12.5, 6.25 and 3.125 µg/mL).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Por otra parte, el uso de fungicidas sintéticos sigue siendo la primera opción en el control de fitopatógenos de importancia agrícola (Zhu et al, 2020). Para el control de Penicillium sp.…”
Section: Antagonismo In Vitro De Levaduras De Origen Marino Hacia P Italicumunclassified
“…Studies have indicated that natural products have unique biological functional diversity and chemical diversity, which give them unique advantages in drug molecular design [6–8] . In recent years, the derivation of molecular structures from natural products has been one of the most effective methods to develop and design drugs with unique mechanisms of action [9,10] . Amino acids are the basic constituent unit of biological macromolecular proteins, are involved in metabolism regulation and information transmission, and play crucial roles in various biological functions [11] .…”
Section: Introductionmentioning
confidence: 99%